THE DEVELOPMENT OF RUSSIAN TRANSNATIONAL CORPORATIONS IN TERMS OF GLOBALIZATION OF THE WORLD ECONOMY - E. Shilets; O. Sokrutenko (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the role and place of Russian TNCs in the global integration process. The features of the economic activity of TNCs in Russia are considered. The main problems of global TNCs are identified, trends in their further development are determinated. The importance of modernizing the restructuring of the world economy for improving the possibilities of importing capital and technologies, increasing competitiveness, increasing the chances for the process of innovative modernization and the search for investments for Russian TNCs has been determined. The study found that the current stage of development of the global economy is characterized by a tendency to increase the number of transnational corporations from countries with emerging markets and transition economies, which is due to the impact of globalization on the Russian economy.